2020
DOI: 10.2147/opth.s283370
|View full text |Cite
|
Sign up to set email alerts
|

<p>Surgical Grade and Repeat Laser Peripheral Iridotomy Procedures with Risk Stratification and Educational Considerations</p>

Abstract: Background/Aims Peripheral laser iridotomy (PLI) is a commonly performed procedure. While effective, repeat procedures (RPs) may be required for a variety of causes. We report the causes and rate of RP PLI and whether surgical grade is a risk factor. Methods Two years of retrospective data from 282 patients who had undergone PLI at a single UK ophthalmology department were retrieved using an electronic medical record system (Medisoft, Leeds, UK). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The Accreditation Council for Graduate Medical Education requires all ophthalmology residents to perform LPI before graduation. Riley et al [13] illustrated that the RP rate for LPI procedures was associated with the experience of the operating surgeon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Accreditation Council for Graduate Medical Education requires all ophthalmology residents to perform LPI before graduation. Riley et al [13] illustrated that the RP rate for LPI procedures was associated with the experience of the operating surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…LPI is indispensable for glaucoma treatment [11][12] . It was reported that the rate of repeat procedures (RPs) for LPI was related to the operating surgeon's level of experience [13] . However, the parameters of LPI were not included in the study to explore how the level of experience contributed to the rate of RPs.…”
Section: Introductionmentioning
confidence: 99%